Modelling the seed bank evolution and emergence of oilseed rape volunteers for managing co-existence of GM and non-GM varieties - Colbach, Nathalie; Dürr, Carolyne; Gruber, Sabine; Pekrun, Carola (European journal of agronomy, 2008)
Gene flow in oilseed rape is a process occurring over the years and large distances and has been the object of several models for evaluating the co-existence of GM and non-GM crops. Oilseed rape volunteers play a major role and the survival, dormancy and emergence of the volunteer seeds left after oilseed rape crops are key processes for gene flow. In the present paper, these processes were analysed and modelled in detail for integration into the GENESYS model, which quantifies the effects of cropping systems on spatio-temporal gene flow. In this model, seed bank dynamics are the result of seed survival, dormancy induction, dormancy cycles, germination processes and pre-emergent shoot growth in soil. These biological processes depend on tillage tools and dates, in interaction with temperature and soil moisture. The model was evaluated by comparing its simulations to independent field data on volunteer emergence after different tillage strategies and in different cropping systems. Finally, the model was used to simulate the effect of tillage strategies on volunteer densities in winter cereals and the adventitious presence of GM seeds in non-GM oilseed rape crops in case of temporal and/or spatial co-existence of GM and non-GM oilseed rape varieties.